Development of an international electronic database for research into neuroimmunological diseases (enid). Issue 5 (8th May 2017) - Buzzard, Katherine; Reddel, Stephen W; Riminton, Sean; Butzkueven, Helmut
Abstract : Objectives: To develop an international registry for patients with neuroimmunological diseases (eNID). The nervous system is vulnerable to inflammatory damage caused by the immune system leading to a variety of neuroimmunological diseases. These diseases are often chronic, requiring long-term management. They are generally treatable, however they are often associated with periods of significant disability. Although individually rare, collectively neuroimmunological diseases affect a significant number of individuals worldwide and account for a disproportionately heavy burden on health care systems. Like so many rare diseases, a lack of evidence-based information poses significant challenges for clinicians. Disease registries can be powerful and cost-effective instruments for expanding our knowledge of diseases and treatments. They are particularly useful in rare diseases where they can provide the opportunity to pool 'real world' data to reach a sufficient sample size for epidemiological and clinical research. Methods: eNID is being built as an extension to MSBase, a highly successful international registry for patients with multiple sclerosis. Four diseases will be initially included: myasthenia gravis, CIDP, neurosarcoidosis and autoimmune encephalitis (AE). Each disease will be represented by a disease specific interest group (DIG) comprising international and national disease experts, who will be responsible for implementing the design of the data templates. The myasthenia gravis database build has commenced after consultation with the DIG. It is anticipated that the registry will start receiving data by May 2017. The AE data template has been established with the build likely to commence June 2017. The CIDP and NS data templates are in progress. Conclusions: eNID will ultimately increase our understanding of the epidemiology, treatment, prognosis and impact of neuroimmunological diseases through collaborative international research, leading to better patient outcomes.